Automatické generování wiki stránek z e-mailů a IS - Vavřínek, Aleš (Vysoké učení technické v Brně. Fakulta informačních technologií, 2011)
Tato diplomová práce se zabývá vytvořením rozšíření pro stávající informační systém NLPIS. Součástí řešení je vytváření a údržba automaticky generovaných stránek pro projekty do aplikace MediaWiki. Data budou do MediaWiki generována z e-mailové komunikace a databáze informačního systému NLPIS.

This master's thesis deals with the creation of an extension to the existing information system NLPIS. A part of solution is the creation and maintenance of automatically generated pages for projects in the MediaWiki application. The data will be generated into the MediaWiki from database NLPIS information system and e-mail communications.
Automatic Generation of Wiki Pages from e-Mails and IS
Keywords: Automatické generování; web; stránka; informační systém; NLPIS; MediaWiki; HTML; CSS; PHP.; Automatic generation; web; page; information system; NLPIS; MediaWiki; HTML; CSS; PHP.